Linguagem fotográfica nas imagens publicitárias da Hope Lingerie: sedução, estésia e programação nas plataformas digitais - Makssoudian, Rogério Armenac (2019)
The research investigates how the photographic images act in the construction of advertising speeches through the semiotic analysis of the photographic language and its generation of meaning in digital platforms of the store Hope Lingerie. This segment is very relevant in the Brazilian economic scenario and in the fashion industry. Moreover, it is mediatically reiterated as a symbolic element of the idea of feminine in the current social scene. The objective is to investigate and understand the values articulated by the imagery and its speeches, as well as to identify and analyze the main enunciative arrangements of the phrases of the photographic system in the Instagram network and the Hope Lingerie website, thus contributing to a better understanding of the relationship between advertising images present in the electronic media and contemporary society. From this problem, the hypotheses were proposed: that the articulations of the elements of the photographic language, by their plastic nature, in their relation with the content, give to see different ways of making the object feel; that such discourses reach recipients in different ways and thus articulate distinct consumption axiologies; that the speech in Instagram is given by the interaction regime of manipulation, under the mode of seduction, while the imagery related to e-commerce tends to the programming regime. The cut for this dissertation is formed by ten advertising images captured between May 1, 2017 and December 31, 2018 in Instagram and in the e-commerce of the store Hope Lingerie. They were analyzed in their contexts under the theoretical framework of discursive semiotics, based on the studies of Algirdas Julien Greimas, with the methodological procedures of the generative path of meaning, in the plastic and figurative semiotics postulated by the same author and by Jean-Marie Floch, and in continuity given by Eric Landowski in the formulation of the regimes of sense and interaction, in addition to the contributions of Ana Claudia de Oliveira regarding visibility and syncretism. Research will therefore contribute to the advancement of the study of enunciation in photography, a determining component of advertising and trade language, in a media environment in which the image is a protagonist and constitutes a simulacrum of the recipient of consumption